Wisdom In AL –Farazdak s Poetry (Journal of the College of Languages (JCL), 2008)
Wisdom in the era before Islam is soo famous and so mature And Wisdom in the age of Islam {the holy quran and AI Hadeeth AI shareef }is dealt with by different meanings that agree with the contexts in which it occurs its contacs One of meanings is wisesaying that occuars in the Halal and Haram .As to the wisdom of the Amawy age ,it was some times absent since it was not dealt with by the great Poets of that age .In the Poetry of AL-FARAZDAK , Wisdom was little and it expressed religious and phsycological meanings because wisdom is amessage that has along –rang .